Glamis Gold, Ltd. v. The United States and the Fair and Equitable Treatment Standard - Ryan, Margaret (McGill Law Journal / Revue de droit de McGill, 2011)
This article critiques the arbitral tribunal’s decision in Glamis Gold, Ltd. v. The United States of America on the basis of its interpretation of the fair and equitable treatment standard (FET) owed by state parties to foreign investors under NAFTA article 1105.Part I outlines the post-WWII development of the FET standard in relation to the restrictive, customary international law of minimum standard of treatment (MST). The author traces the expansive treatment of the FET standard by tribunals in both bilateral investment treaty and NAFTA disputes. Despite a binding Free Trade Commission Note of Interpretation limiting the scope of article 1105, NAFTA tribunals had consistently interpreted the FET standard more broadly until the award in Glamis.Part II evaluates the tribunal’s reasoning in Glamis, arguing that it departs from a growing body of jurisprudence on the FET standard under NAFTA without sufficient justification. The author also criticizes the tribunal’s decision to place an unprecedented evidentiary burden on the claimant by requiring proof of both state practice and opinio juris of the FET standard.The conclusion suggests that the decision of the tribunal in Merrill & Ring Forestry L.P. v. Canada may provide a better approach to balancing governments’ legitimate regulatory objectives and foreign investors’ treaty rights.